STUDI AWAL POLIMERISASI OPAL STIRENA-BUTILAKRILAT BERUKURAN SERAGAM SECARA NANOTEKNOLOGI - Evi Oktavia; Nurudin Budiman; Emil Budianto (JURNAL SELULOSA, 2006)
A preliminary study of starved feed stepwise emulsion polymerization was conducted on two monomers, which have a large refractive index difference between the hard monomer styrene and the soft monomer butyl acrylate. Monomer glycidyl methacrylate used as cross linker agent. These monomers are selected to obtain monodisperse polymer colloids for the preparation of elastomeric polymer opaline film. The films showed opaline color shades due to selective reflection of the light wavelength corresponding to the lattice spacing. Surfactant and initiator were maintained at low concentrations in order to obtain polymer colloids of nanometer size i.e. 200 – 300 nm in diameter. These polymer colloids in range sizes of particles were cast dried. They showed the opalescence colors. The effect of concentration surfactant sodium lauryl sulfate and concentration of initiator ammonium persulfate was investigated to obtain theoretically solid content. The polymers prepared with this method were monodispersed at less than 5 % INTISARI Studi awal polimerisasi emulsi dilakukan terhadap dua monomer dengan perbedaan indeks refraksi yang cukup tinggi, antara monomer keras stirena dan monomer lunak butil akrilat. Monomer glisidil metakrilat digunakan sebagai pengikat silang. Polimer koloid yang dihasilkan mempunyai distribusi ukuran partikel seragam, untuk menghasilkan polimer elastomerik berwarna opal. Warna disebabkan oleh hamburan selektif panjang gelombang sinar yang dilewatkan sebanding dengan jarak kisi kristal koloid. Konsentrasi surfaktan dan inisiator dijaga rendah untuk menghasilkan partikel berukuran nanometer yaitu 200 – 300 nm. Polimer dalam wujud kering berwarna opal. Pengaruh surfaktan natrium lauril sulfat, dan inisiator amonium persulfat diamati untuk mendapatkan kandungan padatan teoritis. Polimer mempunyai distribusi ukuran partikel yang seragam, yaitu dibawah 0,05.